Analisis Kadar Seng (Zn) dan Besi (Fe) Pada Kangkung Air (Ipomoea aquatica Forssk.) Berdasarkan Tempat Tumbuh Dengan Metode AAS (Atomic Absorption Spectrophotometry) - Khoirunnisa, Aishwarya; Nur, Achmad Vandian; Rahmasari, Khusna Santika; WIrasti, Wirasti (Bioma : Berkala Ilmiah Biologi, 2023)
Water spinach (Ipomoea aquatica Forssk.) is a vegetable that is widely found and consumed by the public, containing among others protein, calcium, phosphorus, iron, potassium, zinc and vitamins A, B1 and C. Zn is a micronutrient that functions for growth and development of bone metabolism. Fe is a micromineral for the formation of hemoglobin in the blood. The purpose of this study was to determine the content and amount of zinc and iron in water spinach based on different growing places using the AAS (Atomic Absorption Spectrophotometry) method. The sample used in this study was water spinach (Ipomoea aquatica Forssk.) taken from 3 locations, namely Sapugarut, Coprayan and Kandang Panjang. The method in this study was qualitatively using color testing and quantitatively using AAS. The results of qualitative testing on Fe produced a brownish color and Zn produced a clear solution with a white precipitate. Quantitative test results using the AAS method at a wavelength of 248.3 nm for zinc and 213.9 nm for iron. The Zn content in the sample obtained was sample A of 0.3869 mg/100 g, sample B of 0.5199 mg/100 g and sample C of 0.2556 mg/100 g while the level of Fe in sample A was 2.502 mg/100 g, sample B was 2.275 mg/100 g and sample C was 1.925 mg/100 g. The results of the study showed that the Zn and Fe levels had different levels, this was because the nutrient content in the soil had different nutrients.